L’association des courtiers d’assurances de la province de Québec - Moreau, Rémi (Assurances, 1983)
The author looks at the Association from various angles: the law which governs it, its objectives and powers, how it operates. The reader will thus be able to appreciate the useful function of an association which serves both the interests of the public and of its members. The article also draws attention to the code of conduct which should guide a broker, and give credibility to basic insurance functions.